2007
DOI: 10.1111/j.1471-0528.2006.01201.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of intravenous immunoglobulin for treatment of recurrent miscarriage: a systematic review

Abstract: Background Intravenous immunoglobulin (IVIG) is a fractionated blood product whose off-label use for treating a variety of conditions, including spontaneous recurrent miscarriage, has continued to grow in recent years. Its high costs and short supply necessitate improved guidance on its appropriate applications.Objective We conducted a systematic review of randomised controlled trials evaluating IVIG for treatment of spontaneous recurrent miscarriage. Selection criteria We included all randomised controlled tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
89
2
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(103 citation statements)
references
References 22 publications
(46 reference statements)
6
89
2
5
Order By: Relevance
“…There is also empirical evidence for benefit in patients with recurrent spontaneous abortion if secondary or associated with autoantibodies or elevated natural killer (NK)-lineage cells in blood [2][3][4]. In vitro fertilization failure may also be prevented in patients who have immune abnormalities [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also empirical evidence for benefit in patients with recurrent spontaneous abortion if secondary or associated with autoantibodies or elevated natural killer (NK)-lineage cells in blood [2][3][4]. In vitro fertilization failure may also be prevented in patients who have immune abnormalities [2].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro fertilization failure may also be prevented in patients who have immune abnormalities [2]. Suppression of blood NK cell activity has been proposed as an important effect, and different IVIGs may differ in potency both in vitro and in vivo [3][4][5]. However, the mechanism of IVIG suppression of NK-type cells is uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Hutton et al, in a meta-analysis of placebo-controlled trials of IVIg in RM, found that the OR of achieving a live birth in primary and secondary RM was 0·66 and 2·71, respectively, suggesting that IVIg may be effective in secondary RM patients, but not primary RM patients [16]. A recent meta-analysis of five placebo-controlled studies (Christiansen et al, unpublished data) found that the OR for an unsuccessful pregnancy in secondary RM patients was 0·74 bs_bs_banner Clinical and Experimental Immunology IMMUNOMODUL ATION…”
mentioning
confidence: 99%
“…7,[93][94][95][96][97] Recent meta-analysis reported a significant increase in live births following IVIg use in women with secondary recurrent miscarriage although overall live birth rate was not improved. 98 We have reported that IVIg treatment significantly improved reproductive outcome in women with aPL who were refractory to anticoagulation treatment or elevated NK cell levels. 99,100 In addition, IVIg treatment has been reported to be effective in RPL women with aPL with catastrophic APS.…”
Section: The Epitopes Of Apl and Treatment Outcomementioning
confidence: 92%